Neoadjuvant stereotactic radiosurgery for intracerebral metastases of solid tumors (NepoMUC): A phase i dose escalation trial - Diehl, Christian D.; Shiban, Ehab; Straube, Christoph; Gempt, Jens; Wilkens, Jan J.; Oechsner, Markus; Kessel, Carmen; Zimmer, Claus; Wiestler, Benedict; Meyer, Bernhard; Combs, Stephanie E. (Cancer Communications, 2019)
Background: More than 25% of patients with solid cancers develop intracerebral metastases. Aside of surgery, radiation therapy (RT) is a mainstay in the treatment of intracerebral metastases. Postoperative fractionated stereotactic RT (FSRT) to the resection cavity of intracerebral metastases is a treatment of choice to reduce the risk of local recurrence. However, FSRT has to be delayed until a sufficient wound healing is attained; hence systemic therapy might be postponed. Neoadjuvant stereotactic radiosurgery (SRS) might offer advantages over adjuvant FSRT in terms of better target delineation and an earlier start of systemic chemotherapy. Here, we conducted a study to find the maximum tolerated dose (MTD) of neoadjuvant SRS for intracerebral metastases. Methods: This is a single-center, phase I dose escalation study on neoadjuvant SRS for intracerebral metastases that will be conducted at the Klinikum rechts der Isar Hospital, Technical University of Munich. The rule-based traditional 3 + 3 design for this trial with 3 dose levels and 4 different cohorts depending on lesion size will be applied. The primary endpoint is the MTD for which no dose-limiting toxicities (DLT) occur. The adverse events of each participant will be evaluated according to the Common Terminology Criteria for Adverse Events (CTCAE) version 5.0 continuously during the study until the first follow-up visit (4-6 weeks after surgery). Secondary endpoints include local control rate, survival, immunological tumor characteristics, quality of life (QoL), CTCAE grade of late clinical, neurological, and neurocognitive toxicities. In addition to the intracerebral metastasis which is treated with neoadjuvant SRS and resection up to four additional intracerebral metastases can be treated with definitive SRS. Depending on the occurrence of DLT up to 72 patients will be enrolled. The recruitment phase will last for 24 months. Discussion: Neoadjuvant SRS for intracerebral metastases offers potential advantages over postoperative SRS to the resection cavity, such as better target volume definition with subsequent higher efficiency of eliminating tumor cells, and lower damage to surrounding healthy tissue, and much-needed systemic chemotherapy could be initiated more rapidly. Trial registration The local ethical review committee of Technical University of Munich (199/18S) approved this study on September 05, 2018. This trial was registered on German Clinical Trials Register (DRKS00016613; https://www.drks.de/drks_web/navigate.do?navigationId=trial.HTML&TRIAL_ID=DRKS00016613) on January 29, 2019.
CRIS-Team Scopus Importer:2023-03-08
Keywords: Cancer; Fractionated stereotactic radiation therapy; Intracerebral metastasis; Maximum tolerated dose; Microsurgical resection; Neoadjuvant radiation therapy; Protocol; Stereotactic radiosurgery